Systematic approach to boulder stability assessment at a boulder covered area: case study at Gunung Bujang Melaka, Kampar, Perak - Tan, Jia Qi; Norasiah Sulaiman; Nor Shahidah Mohd Nazer; Muhammad Taqiuddin Zakaria; Nurul ‘Amalina Md Nor; Askury Abd Kadir; Abdul Ghani Rafek; Ailie Sofyiana Serasa; Lee, Khai Ern; Goh, Thian Lai (Penerbit Universiti Kebangsaan Malaysia, 2025)
Gunung Bujang Melaka is set to be developed into a tourist attraction, prompting a study of the granite boulders in the area to ensure visitor safety. This paper aimed to identify potential unstable boulders and produce a stability zonation map of the designated area. Aerial photogrammetry was conducted to create a 3D model of the project area, capturing the boulders’ characteristics. Each boulder was delineated using 3D processing software-ShapeMetrix-to acquire dimensions, base dipping angles, and azimuths. The general slope angle of the project area was generated using the moving average grid method on the digital elevation model (DEM) produced from the 3D model. Tilt tests were performed on-site, showing a basic frictional angle of 30° and a peak frictional angle of 66°. Over 1,600 boulders were identified across the area, with 274 boulders having visible base angles evaluated using kinematic analysis and the Hoek & Bray block model for stability assessment. The results indicated five types of boulder stability: Exceptionally Stable (8, 3%), Very Stable (102, 37%), Stable (16, 6%), Likely Stable (126, 46%) and Potential Sliding (22, 8%). The remaining boulders, with their base planes concealed by surrounding boulders, were considered interlocking due to deep-seated and support from adjacent boulders. Mitigation measures such as bracing and anchoring are recommended based on their modes of failure.